Redistribution from a lifetime perspective - Peter Levell; Barra Roantree; Jonathan Shaw (Institute for Fiscal Studies (IFS), 2015)
Most analysis of the effects of the tax and benefit system is based on snapshot information about a single cross-section of people. Such an approach gives only a partial picture because it cannot account for the fact that circumstances change over life. This paper investigates how our impression of redistribution undertaken by the tax and benefit system changes when viewed from a lifetime perspective. To do so, we simulate lifecycle data designed to be representative of the experiences of the baby-boom cohort, born 1945-54. We examine the properties of the current tax and benefit system as well as historical and hypothetical reforms from both a lifetime and a snapshot perspective. We find that much of what the tax and benefit system achieves is effectively to redistribute across periods of life and, as a result, it is much less effective at reducing lifetime inequality than inequality at a snapshot.
Keywords: 330